Clinician Communication With Patients About Cancer Misinformation: A Qualitative Study. Issue 3 (10th March 2023) - Bylund, Carma L.; Mullis, Michaela D.; Alpert, Jordan; Markham, Merry Jennifer; Onega, Tracy; Fisher, Carla L.; Johnson, Skyler B.
Abstract : PURPOSE: Clinicians regularly face conversations about information that patients have found online. Given the prevalence of misinformation, these conversations can include cancer-related misinformation, which is often harmful. Clinicians are in a key position as trusted sources of information to educate patients. However, there is no research on clinician-patient conversations about cancer-related misinformation. As a first step, the objective of this study was to describe how cancer clinicians report communicating with patients about online cancer misinformation. METHODS: We used convenience and snowball sampling to contact 59 cancer clinicians by e-mail. Contacted clinicians predominately worked at academic centers across the United States. Clinicians who agreed participated in semistructured interviews about communication in health care. For this study, we focused specifically on clinicians' experiences discussing online cancer-related misinformation with patients. We conducted a thematic analysis using a constant comparative approach to identify how clinicians address misinformation during clinical visits. RESULTS: Twenty-one cancer clinicians participated in the study. Nineteen were physicians, one was a physician assistant, and one was a nurse practitioner. The majority (62%) were female. We identified four themes that describe how cancer clinicians address misinformation: (1) work to understand the misinformation; (2) correct misinformation through education; (3) advise about future online searches, and (4) preserve the clinician-patient relationship. CONCLUSION: Our study identified four strategies that clinicians use to address online cancer-related misinformation with their patients. These findings provide a foundation for future research, allowing us to test these strategies in larger samples to examine their effectiveness.